A "Safe Space" to Debate Colonial Legacy: The University of Cambridge Museum of Archaeology and Anthropology and the Campaign to Return a Looted Benin Altarpiece to Nigeria. Issue 1 (1st July 2019) - Zetterstrom-Sharp, Johanna; Wingfield, Chris
Abstract : In February 2016, students at Jesus College, Cambridge voted unanimously to repatriate to Nigeria a bronze cockerel looted during the violent British expedition into Benin City in 1897. The college, however, decided to temporarily relocate Okukor to the University's Museum of Archaeology and Anthropology. This article outlines the discussions that occurred during this process, exploring how the Museum was positioned as a safe space in which uncomfortable colonial legacies, including institutionalized racism and cultural patrimony rights, could be debated. We explore how a stated commitment to postcolonial dialogue ultimately worked to circumvent a call for postcolonial action. Drawing on Ann Stoler's and Elizabeth Edwards's discussions of colonial aphasia, this article argues that anthropology museums risk enabling such circumvention despite confronting their own institutional colonial legacies.